Combination of Coagulation and Fermentation Technology in Utilizing Liquid Tofu Waste into Liquid Organic Fertilizer for the Growth of Chinese Spinach (Amaranthus dubius) Plants - Nina Arlofa; Dama Satya Kusuma; Dwiyan Arya Nugraha; Mochammad Rizal Laksana (Helium: Journal of Science and Applied Chemistry, 2025)
Wastewater is known to contain organic compounds, such as proteins, fats, and carbohydrates, which can be utilized more effectively through technology, coagulation, and fermentation, allowing it to be used as an organic liquid fertilizer (OLF), a more environmentally friendly option. Research objectives are to determine the influence of powder seed sour Java as a coagulant on lower COD and BOD levels, the effect of adding EM4 to nutrients in waste liquid, and the impact of POC on the growth of spinach China (Amaranthus dubius). This research is conducted through the process of coagulation and flocculation using a solution seed powder of sour Java with varying concentrations of 500, 1000, 1500, 2000, and 2500 ppm. The concentration of 1500 ppm has resulted in the lowest COD and BOD levels, respectively, 250 ppm and 127 ppm. The solution with the lowest COD and BOD levels is fermented using EM4 with variations of 0, 0.5, 1, 1.5, and 2mL. The addition of EM4 is expected to accelerate the fermentation process and enhance the availability of beneficial nutrients, including N, P, and K, for plant growth and development. The total content of N, P, and K is highest, at 2.087%, following the addition of 1 mL of EM4 to 150 mL of the sample. POC with the addition of 1 mL of EM4 was applied to the spinach plant in China, resulting in a plant 25 cm tall, with nine leaves, and a total fresh weight of 39 grams.